HUBUNGAN ANTARA PERUBAHAN IKLIM DAN PRODUKSI TANAMAN PADI DI LAHAN RAWA SUMATERA SELATAN - Khodijah NS (Program Studi Agroteknologi, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2015)
Tidal swamp areas in Indonesia have important role and strategic for agricultural development, especially to support national food security. It has a potency, land productivity and management technology. Tidal swamp land have a large area which potentially used as agricultural land, especially for rice. There are constraints for agriculture in tidal swamp areas, such as: (1) low soil fertility, (2) infrastructure is not optimally function, (3) low education farmer, (4) harvest index once a years, dan (5) high pest attacks. Total damages and losts effected by climate change, such as flood and drought, increase time by time. Because tidal swamp areas have different characteristic, we need information about the condition in an extreme climate change and its damages causes yield loses in tidal swamp areas. The rereach aimed to identify relatedness between climate change and crop production in tidal swamp areas, especially in South Sumatera. Climatic factor which giving effect to production, harvest area and rice productivity in South Sumatera from 2000 to 2012 is rainfall. It means that water availability will greatly effect the production, harvest area, and rice productivity. Sunlight and temperature have not a big role to increase production, harvest area and productivity, but there is increasing trend in temperature and lighting give effect to production, harvest area and rice productivity. Otherwise, high humidity gives effect in decreasing production, harvest area and rice productivity.